XR Programmers Give Their Perspective on How XR Technology can be Effectively Utilised in High-Performance Sport - Peter J. Le Noury; Remco C. Polman; Michael A. Maloney; Adam D. Gorman (SpringerOpen, 2023)
Abstract Background The successful use of extended reality (XR) in sport is highly dependent on the extent to which it can represent the perception-action couplings that exist in the performance setting. However, there are many unknowns regarding the effectiveness of XR technology which is limiting its adoption in sport. Therefore, providing high-performance sporting organisations with more information about the efficacy and utility of XR, specifically its strengths and limitations, is warranted. Results The results provide insight into the limitations of XR and how those limitations are likely to reduce the effectiveness of XR for training motor skills. The participants described opportunities provided by XR for measuring athlete performance and highlighted several practical applications for enhancing athlete and coaching performance. Using artificial intelligence (AI) for training tactical decision-making and creating new movement solutions was also a key finding. Conclusions The use of XR in sport is in its infancy, and more research is required to establish a deeper understanding of its utility and efficacy. This research provides sporting organisations, coaches, athletes, and XR technology companies with insights into where XR technology can have the greatest positive impact on performance in sport.